Identitas dalam Hubungan Internasional: Dilema Kebijakan Luar Negeri Finlandia Dalam Krisis Ukraina 2014 - Margareth, Fitri Kamelia; Utomo, Tri Cahyo; Rosyidin, Mohamad (Journal of International Relations, 2017)
This research aims to explain why Finland did not play role as peacemaker in UkraineCrisis. The great contribution on mediating conflicts in international relation has made Finland plays role as peacemaker, a country who being well known with their peace action.But as Ukraine Crisis occurs, Finland only helps by sending foreign aid and giving advice toRussia and Ukraine to arrange a mediation, without present itself as the mediator. Usingconstructivist approaches, this research argues that there is identity conflict betweenFinland’s identity as a peacemaker and as a member of The European Union which isagainst Russia. The strong solidarity between The European Union and Finland causedFinland tends to support The European Union’s decision to impose economic sanctionagainst Russia, instead of mediating the conflict. This research confirms a constructivist assumption that states must consider their identities in determining foreign policy, so they will not turned dilemma when they face a situation where they need to use more than one identity to conduct foreign policy.